2012
DOI: 10.5370/jeet.2012.7.4.493
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of GA, DE, PSO and SA Approaches in Enhancement of Total Transfer Capability using FACTS Devices

Abstract: -In this paper the performance of meta-heuristics algorithms such as GA (Genetic Algorithm), DE (Differential Evolution), PSO (Particle Swarm Optimization) and SA (Simulated Annealing) for the problem of TTC enhancement using FACTS devices are compared. In addition to that in the assessment procedure of TTC two novel techniques are proposed. First the optimization algorithm which is used for TTC enhancement is simultaneously used for assessment of TTC. Second the power flow is done using Broyden -Shamanski met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…one point crossover, which is normally used in the GA. However, the GA was outperformed by the differential evolution (DE) algorithm in terms of global search ability [44,45]. Li and Zhang [46], Li and Zhang [47] proposed a multi-objective differential evolution based decomposition (MODE/D) in which the genetic operator was replaced by the differential operators and revealed that the MODE/D performed better than several other MOEAs on many test problems.…”
Section: Amoea/d-dementioning
confidence: 99%
“…one point crossover, which is normally used in the GA. However, the GA was outperformed by the differential evolution (DE) algorithm in terms of global search ability [44,45]. Li and Zhang [46], Li and Zhang [47] proposed a multi-objective differential evolution based decomposition (MODE/D) in which the genetic operator was replaced by the differential operators and revealed that the MODE/D performed better than several other MOEAs on many test problems.…”
Section: Amoea/d-dementioning
confidence: 99%
“…Finding the most optimum system configuration consider both a technical aspect and economical aspect, an optimization method or optimization algorithm is needed in search of the global optimum e.g. genetic algorithm (GA), particle swarm optimization (PSO) algorithm and differential evolution (DE) Algorithm [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In [5][6] [8], which used genetic algorithms to size optimal PV/Wind/batteries hybrid systems by minimizing LPSP and the ACS. The studied showed genetic algorithms made possible to calculate the number of the components of the optimal configuration which ensure a cover of the load with an acceptance of an LPSP.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests that meta-heuristic algorithms such GA, DE, and PSO produce consistently better results than conventional tuning techniques with DE outperforming the other algorithms in results and computational cost [3].Furthermore, Kachitvichyanukul [2], in a comparison of the three algorithms, concluded that GA falls into local minima with greater tendency than the other algorithms, while PSO tends to result in higher density of solutions within the solution space with DE being closely comparable to PSO.…”
Section: Introductionmentioning
confidence: 99%